PROFIL KEMAMPUAN PEMECAHAN MASALAH BIOLOGI SISWA SMA DI KOTA MATARAM - Karmana, I Wayan (Bioscientist : Jurnal Ilmiah Biologi, 2014)
This research includes descriptive research type which aimed to describe profile problem solving ability of high school student in Mataram City. As a sample of research are students of SMAN 3, SMAN 6, SMAN 7, and SMAN 8 Mataram. Data were collected using a problem-solving test. The collected data were analyzed descriptively qualitatively using percentage and mean then categorized qualitatively. From the result of research known that problem solving ability of high school student in Mataram City still categorize less and medium (specially taught by PBL) and not yet reached the level of category good and very good.